Vector-borne diseases epidemiology and control - Tyagi, B. K. (Scientific Publishers, India on behalf of Centre for Research in Medical Entomology, ICMR, 2008)
Contributed papers presented at the 8th International Symposium of Vectors & Vector-borne Diseases during 13-15 October, 2006 at CRME, Madurai, India.